Weak reduction and garbage collection in interaction nets - Pinto, Jorge Sousa (2003)
This paper presents an implementation device for the weak reduction of interaction nets to interface normal form. The results produced by running several benchmarks are given, suggesting that weak reduction greatly improves the performance of the interaction combinators-based implementation of the λ-calculus.